RTEV - ambiente de desenvolvimento de aplicações reconfiguráveis com o kernel de tempo real Virtuoso - Andrade, Mairum Ceoldo (Universidade Federal de São Carlos, 2006)
This dissertation presents an environment for the development of reconfigurable applications, with Virtuoso Real-Time Kernel, called RTEV. This work is based on the TEV (Teaching Environment for Virtuoso), developed at DC/UFSCar (Department of Computation of the Federal University of Sao Carlos). In RTEV, it is possible to carry through the development of applications only selecting a reconfigurable function from the library of available functions and making the interconnections with other functions of the applications. It will be presented, for better understanding: a reconfigurable computer review; development methods of functions and/or applications that can be used for the construction of the reconfigurable library; the systems used in the development environment RTEV; and a case study as a way of validation of the development environment. This environment allows the programmers, without any reconfigurable hardware knowledge, to develop applications with reconfigurable components.
Keywords: Computação reconfigurável; FPGA - Field Programable Gate Array; Virtuoso (Sistema operacional de computador); Tempo real; CIENCIAS EXATAS E DA TERRA::CIENCIA DA COMPUTACAO